Medieval Krakow and its Churches: Structure and Meanings - Węcławowicz, Tomasz (Lidé města, 2007)
The first part of this paper aims to analyze the pattern of the network of Krakow town churches in the Romanesque and Gothic periods and studies the role of these individual components of urban landscape taking into account the significance of their dedications (patrocinia) in the symbolic space of the town. The rocky (Wawel) Hill, rising among the meanders of the Vistula River, constitutes the centre of Krakow. Since the very end of the 10th century it was the seat of the bishops and the ducal residence, and later it became the main residence of the Polish kings. In the Romanesque period ten churches and chapels were built here: the cathedral complex consisted of the baptistery chapel and two basilicas, and seven other small churches and chapels according to the concept developed in the early Middle Ages following the exegesis of the apocalyptic vision of St John the Evangelist. Beneath the castle, along the main trade routes, four churches were founded in modo cruces. Some historians have suggested that the idea of a cruciform layout came from Prince Kazimir, known as the Restorer. In the second half of the 11th century the prince intended to re-create in his capital the layout of the imperial seat in Aachen, an arrangement rich in powerful association. At the end of the 12th century, three more churches dedicated to the Roman Martyrs were founded in Krakow simultaneously as an attempt to re-invent the city as a similitudo Romae in its Early Christian glory. The second part of this paper explains the distinguishing features of the cathedral church and other churches in town and argues that iconographic analysis of their architecture helps to explain their unique character and appearance. During the 14th century the cathedral church was quickly becoming one the most important in the Kingdom, the true Königskirche. The idea of Christian Kingship was an important part of their iconographic program. Also the monumental basilical churches in town can be seen as a manifestation of Kingdom and Kingship. In contrast to the importance of the monumental basilical churches, the meanings of the small hall churches concentrated more on the devotion aspects. Towards the end of the Middle Ages the city space gradually took on new symbolic meanings connected with the cathedral church as the sanctuary of St Stanislaw, Pater Patriae – the primary political patron of Poland.